2011
DOI: 10.1245/s10434-011-1646-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Increased Experience with Isolated Limb Infusion for Advanced Limb Melanoma Influence Outcome? A Comparison of Two Treatment Periods at a Single Institution

Abstract: Response rates and survival following ILI for advanced melanoma in our late treatment period were similar to those of our early treatment period, despite the significantly greater tumor load of the patients treated in the late period. This could be attributed to increased experience and protocol modifications, which allowed longer drug exposure times and higher limb temperatures to be achieved without increased toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Twenty percent of the ILI cohort also developed ≥ Grade 3 Wieberdink toxicity, whereas ILP was associated with a 27% risk of ≥ Grade 3 toxicity <25>. The Sydney Melanoma Unit recently reported a 0% limb loss rate with ILI for melanoma, but observed a 35% rate of ≥ Grade 3 toxicity <26>. Santillan et al found toxicity after ILI to be associated with female sex, papaverine, and high peak CK levels.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of the ILI cohort also developed ≥ Grade 3 Wieberdink toxicity, whereas ILP was associated with a 27% risk of ≥ Grade 3 toxicity <25>. The Sydney Melanoma Unit recently reported a 0% limb loss rate with ILI for melanoma, but observed a 35% rate of ≥ Grade 3 toxicity <26>. Santillan et al found toxicity after ILI to be associated with female sex, papaverine, and high peak CK levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments may include isolated limb infusion (ILI) or intralesional injection with substances such as interleukin-2 [18,19] and other agents [20]. ILI is less invasive, allows for shorter surgery and perfusion times and uses lower temperatures and might be an option for patients in otherwise limited medical and cardiac condition.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that ILI produced outcomes and duration of response comparable to HILP(15). A recently updated publication by the MIA showed a slightly decreased ORR of 77% for their more recent ILIs; however, no significant survival differences were observed (16). …”
Section: Discussionmentioning
confidence: 99%